EXPERIENCE OF OUTPATIENT SERVICES IN THE CONTEXT OF A NEW CORONAVIRUS INFECTION - Болгова, Ирина Владимировна; Завразина, Марина Вячеславовна; Черданцева, Людмила Георгиевна; Елгина, Светлана Ивановна; Мозес, Вадим Гельевич; Рудаева, Елена Владимировна; Мозес, Кира Борисовна (Medicine in Kuzbass, 2020)
Aim – to determine the effectiveness of outpatient services in the context of a new coronavirus infection.Materials and methods. The main indicators of the outpatient service after the Conversion of the regional perinatal center into an infectious diseases hospital for patients were studied retrospectively.Results. Considering the volume of consulted patients for the period from April to September 2020, the dynamics decreased. About 22.0 % of pre-registered patients do not come to the appointment, and the population is afraid of getting infected. Analyzing the nosological structure of the patients accepted by the polyclinic doctors, an increase in the severity of the treated patients subject to emergency hospitalization was noted. Significantly increased (by 48.0 %) the load on the shop service of the polyclinic, as employees are examined before starting work in the infectious diseases hospital and after it.Conclusion. Despite the difficult epidemiological situation and concerns of the population, specialized care for adults and children by doctors of the outpatient service of the regional perinatal center continues.
Keywords: outpatient services; adults and children